Efficacy of AAV serotypes to target Schwann cells after intrathecal and intravenous delivery - A. Kagiava; J. Richter; C. Tryfonos; M. Leal-Julià; I. Sargiannidou; C. Christodoulou; A. Bosch; K. A. Kleopa (Scientific Reports, 2021)
Abstract To optimize gene delivery to myelinating Schwann cells we compared clinically relevant AAV serotypes and injection routes. AAV9 and AAVrh10 vectors expressing either EGFP or the neuropathy-associated gene GJB1/Connexin32 (Cx32) under a myelin specific promoter were injected intrathecally or intravenously in wild type and Gjb1-null mice, respectively. Vector biodistribution in lumbar roots and sciatic nerves was higher in AAVrh10 injected mice while EGFP and Cx32 expression rates and levels were similar between the two serotypes. A gradient of biodistribution away from the injection site was seen with both intrathecal and intravenous delivery, while similar expression rates were achieved despite higher vector amounts injected intravenously. Quantified immune cells in relevant tissues were similar to non-injected littermates. Overall, AAV9 and AAVrh10 efficiently transduce Schwann cells throughout the peripheral nervous system with both clinically relevant routes of administration, although AAV9 and intrathecal injection may offer a more efficient approach for treating demyelinating neuropathies.